Information asymmetry in insurance firms and supervisory institutions relations: problems, consequences and remedies - Kurek, Robert (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2014)
The study presents information asymmetry characteristics in a relation between supervisioninstitution and insurance firm, discusses reasons for this phenomenon occurring, analyses thepossible effects for individual insurance firms and the entire market and also indicates thepossibilities and methods for eliminating its negative consequences.Due to the fact that a supervisory on institution has access to all information regarding aninsurance firm under assessment, information asymmetry in the relation between a supervisoryauthority and an insurance company, by definition, should not take place. However, the performedresearch into this phenomenon indicates that some of its symptoms can be observed, which resultsfrom imperfections ingrained in the information itself, from the cognitive limitations of supervisoryinstitutions staff (decision makers), as well as the indirect implementation, by a supervisoryinstitution, of the information disclosed by insurance firms on a voluntary basis. The consequencesof information asymmetry may become the reason for an improperly performed assessment by thesupervision authority and may influence the decisions made.The performed analysis also puts an emphasis on the fact that classically describedinformation asymmetry effects, such as adverse selection and moral hazard, in cases ofasymmetry occurrence in the relations between a supervisory institution and an insurancecompany, should be supplemented by a costly verification of the current situation (collectinginformation and its credibility verification) which, depending on the scale, is significant forsupervisory authorities in the process of the performed assessment and in taking due decisions,as well as for the proper allocation of the resources at the disposal of insurance institutions andalso for the correct functioning of the entire insurance market.Each area of information asymmetry, in relations between a supervision institution and aninsurance firm, generates a different type of protection possibilities against its occurrence, itsreduced scope and for minimizing its effects, which has also been discussed in the study. Due to thefact that legal regulations and information submission arrangements are not capable of eliminatingall information limitations for asymmetry occurrence to be correctly identified, it is necessary tokeep monitoring all information processes taking place in relations between a supervisioninstitution and an insurance firm. An indispensable condition for eliminating the limited capacity inrecognizing insurance companies’ attributes by supervision authorities, is studying the influence ofall new regulations and researching the phenomena influencing the course of the supervisoryprocesses. However, the fact that a different (larger) information scope is available for asupervisory institution does not necessarily have to influence the decisions made by this institution.
Argumenta Oeconomica, 2014, Nr 2 (33), s. 145-170
Keywords: information; information asymmetry; insurance supervision